Soil chemical properties in abandoned Mediterranean cropland after succession and oak reforestation - Cuesta, B.; Rey Benayas, J. M.; Gallardo, A.; Villar-Salvador, P.; González-Espinosa, M. (Acta Oecologica, 2012)
Large extents of cropland have been abandoned in recent decades and more may be abandoned in the near future. These may undergo secondary succession or reforestation. We experimentally tested the response of soil chemical properties to secondary succession (old ﬁeld) and to Quercus ilex plantation (reforested cropland) in a Mediterranean cropland that was abandoned 13 years ago. We also evaluated the relevance of previous reforestation management (four combinations of presence and absence of irrigation and shading) in addition to current environmental conditions (herbaceous community and cover of oak canopy) on soil chemistry in the reforested cropland. Carbon and NH4 þ eN concentrations and availability of mineral N were higher in the reforested cropland than in the old ﬁeld. However, soil pH, total N, P, K and NO3 eN concentrations, mineralization rates, and available PO4 3 eP were similar in the reforested cropland as well as in the old ﬁeld. Previous reforestation management practices, particularly irrigation, and current environmental conditions, mostly biomass and composition of the herbaceous community, affected soil chemistry. Irrigation increased K and P concentrations and NH4 þ eN availability. This study highlights the overall slow dynamics of soil chemistry in Mediterranean ecosystems, which has resulted in little variation of soil properties in reforested cropland after more than a decade. Reforestation can accelerate the recovery of some soil properties of abandoned cropland in comparison with secondary succession, but these effects will be more noticeable in longer time periods.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: ammonium; Inorganic nitrogen; nitrate; Old ﬁelds; Quercus ilex; Soil fertility; Tree planting